Addendum to "A Review of the History and the Current Practice of Aid Evaluation" - Sasaki, Ryoh (Journal of MultiDisciplinary Evaluation, 2007)
In the article in the previous issue of JMDE, September 2006, “A Review of the History and the Current Practice of Aid Evaluation,” I stated “the EU does not have a unified evaluation approach, because a different EU member agency takes the lead in each evaluation project.” At the time when I accessed the webpage of Europe Aid Co-operation Office (AIDCO), the guidelines of evaluation were not available. The Webpage simply stated “the methodology pages will be available in English, French and Spanish and will be accessible early 2006.” It can be found at: http://ec.europa.eu/europeaid/evaluation/methodology)